2008
DOI: 10.1038/jcbfm.2008.59
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inhibitor of Metalloproteinases Protect Blood—Brain Barrier Disruption in Focal Cerebral Ischemia

Abstract: Enhanced matrix metalloproteinases (MMPs) can cause vasogenic edema and hemorrhagic transformation after cerebral ischemia, and affect the extent of ischemic injury. We hypothesized that the endogenous MMP inhibitors, tissue inhibitor of MMPs (TIMPs), were essential to protect against blood-brain barrier (BBB) disruption after ischemia by regulating the activities of MMPs. We confirmed the transition of MMP-2 and MMP-9, and the TIMPs family after 30 mins of middle cerebral artery occlusion, and elucidated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 43 publications
5
99
1
Order By: Relevance
“…Increased MMP-9 expression and gelatinolytic activity that was accompanied by increased blood-brain barrier (BBB) disruption, neuronal apoptosis, and ischemic injury was reported in 30-minute focal cerebral ischemia-induced TIMP-1 knockout mice [24]. In agreement with these studies, our recent studies in a rat model of transient focal cerebral ischemia and reperfusion reported the post-ischemic induction of MMP-9 activity through gelatin zymography analysis [4,5].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Increased MMP-9 expression and gelatinolytic activity that was accompanied by increased blood-brain barrier (BBB) disruption, neuronal apoptosis, and ischemic injury was reported in 30-minute focal cerebral ischemia-induced TIMP-1 knockout mice [24]. In agreement with these studies, our recent studies in a rat model of transient focal cerebral ischemia and reperfusion reported the post-ischemic induction of MMP-9 activity through gelatin zymography analysis [4,5].…”
Section: Discussionsupporting
confidence: 70%
“…Our recent studies demonstrated the predominant upregulation of MMP-12 and its pathological role in acute brain damage after ischemic stroke [4,5]. The temporal expression profile of various MMPs in ischemic rat brains after focal cerebral ischemia and reperfusion revealed that MMP-9 and MMP-12 were upregulated (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) fold in case of MMP-9 and 47-265 fold in case of MMP-12 through days 1 to 7 after reperfusion) several fold higher than any other MMPs tested [4]. Evidence also suggests the detrimental role of MMP-9 and MMP-12 on post-stroke brain damage [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…During the subsequent synapse stabilization phase, MMP attenuation would support the re-emergence of substrate proteins which anchor new synaptic junctions. Early elevation of secreted MMPs is well documented during neuroplasticity in models of neurotrauma, including controlled cortical impact, and lateral fluid percussion injury, as well as after olfactory bulb lesion, and cerebral ischemia (Costanzo and Perrino, 2008;Costanzo et al, 2006;Fujimoto et al, 2008;Romanic et al, 1998;Truettner et al, 2005;Wang et al, 2000). For example, diffuse percussive TBI elevates MMP-9 within 4 h post-injury, with peak expression at 1-3 days for MMPs 2 and 9 (Truettner et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Mice without TIMP-2 gene showed increased BBB leakage and apoptosis without any change in the ischemic damage. TIMP-1 could be a potential target of neuroprotective therapy [144]. Also, the increase of the MMP9/TIMP1 ratio is significantly associated with symptomatic HT [145].…”
Section: Delayed Htmentioning
confidence: 99%